DNS on Windows Server 2003 - Allen, Robbie (O'Reilly, 2011)
DNS on Windows Server 20003 is a special Windows-oriented edition of the classic DNS and BIND, newly updated to document the many changes to DNS, large and small, found in Windows Server 2003. Veteran O'Reilly authors, Cricket Liu, Matt Larson, and Robbie Allen explain the whole system in terms of the new Windows Server 2003, from starting and stopping a DNS service to establishing an organization's namespace in the global hierarchy.